2021
DOI: 10.1101/2021.04.04.438376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneous but not random: Cargo degradation in phagosomes is kinetically coupled to their intracellular mobility

Abstract: Phagosome maturation, in which ingested pathogens are degraded through a complex sequence of biochemical changes, is an essential process in infection control and tissue homeostasis. The maturation of phagosomes requires their intracellular transport. However, mechanisms underlying this dynamical-biochemical interdependence is poorly understood due to the lack of methods to independently manipulate either process. Here we present a study to magnetically manipulate the transport of single phagosomes and simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 109 publications
(209 reference statements)
0
4
0
Order By: Relevance
“…S1 ). The SAv serves as a cushion layer to separate the pHrodo Red dye from the particle surface, as we observed that pHrodo Red becomes insensitive to pH changes when directly conjugated on particles ( 25 ). From fluorescence images, we confirmed the anisotropic presentation of SAv and IgG on pHMoon particles ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…S1 ). The SAv serves as a cushion layer to separate the pHrodo Red dye from the particle surface, as we observed that pHrodo Red becomes insensitive to pH changes when directly conjugated on particles ( 25 ). From fluorescence images, we confirmed the anisotropic presentation of SAv and IgG on pHMoon particles ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…At each pH, the fluorescence emission of pHrodo Red and CF640R was acquired using epifluorescecnce microscopy. Intracellular pH calibration of pH sensors was done following a previously published protocol ( 25 , 26 ). RAW 264.7 cells stably expressing actin-GFP were seeded as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations